Smallholder farmers’ awareness and perceptions of climate change in Adama district, central rift valley of Ethiopia - Hurgesa Hundera (Weather and Climate Extremes, 2019)
Rural smallholder farmers, who exercise rain fed agriculture for their livelihoods, make up the largest proportion in Ethiopia. This article examined the awareness and perception of rural smallholder farmers about climate change in Adama district, central rift valley region of Ethiopia. Primary data were collected from 351 sample smallholder farmers through questionnaires. Focus group discussions and key informant interviews were also employed. The result revealed that though the majority of smallholder farmers reported that they were aware of climate change, it has been found out that they have limited knowledge about climate change impacts and threats posed to various climate sensitive sectors, for example, agriculture, water, energy etc. The result also indicated that majorities of the respondents perceived that climate is changing. Smallholder farmers of rural areas should get relevant and up-to-date climate change information services. It has also been recommended that national meteorological agency and agricultural office of the district should reach the mass and provide training for the rural farming communities. Keywords: Adama district, Awareness, Climate change, Farmers, Perception, Smallholder